Peran Sukiman Wirjosandjojo dalam Partai Syarikat Islam Indonesia (1927-1933) - Hani Nurhasanah; Nuraeni Marta; Muhammad Hasmi Yanuardi (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
This study aims to examine the role of Sukiman Wirjosandjojo in the development of the Islamic Union Party (PSI) and his contribution to the dynamics of Indonesia’s national movement during the transitional period between nationalist ideas and religious-based struggles. The research applies a historical method with a descriptive-narrative approach. The study follows heuristic steps to trace primary and secondary sources, source criticism both internally and externally, interpretation through analysis and synthesis, and systematic historiography writing. The results show that Sukiman Wirjosandjojo played a strategic role as a bridge between secular nationalist groups and Islamic-based parties. He actively strengthened PSI during its period of decline, contributed to the establishment of the national political federation (PPPKI), and defended workers’ rights through his leadership in the PPPH. Sukiman’s moderate and conciliatory stance caused internal friction within PSI, which culminated in his dismissal and suspension, although many considered these measures unfair. This research affirms that Sukiman deserves to be recognized as a Muslim nationalist figure consistently fighting for Indonesian unity and independence. Penelitian ini bertujuan untuk mengkaji peran Sukiman Wirjosandjojo dalam perkembangan organisasi Partai Syarikat Islam (PSI) dan kontribusinya dalam dinamika pergerakan nasional Indonesia pada masa peralihan antara ide kebangsaan dan perjuangan berbasis agama. Metode yang digunakan adalah metode sejarah dengan pendekatan deskriptif-naratif. Penelitian ini menempuh langkah-langkah heuristik untuk penelusuran sumber primer dan sekunder, kritik sumber secara internal dan eksternal, interpretasi melalui analisis dan sintesis, serta penyusunan historiografi yang sistematis. Hasil penelitian menunjukkan bahwa Sukiman Wirjosandjojo memainkan peran strategis sebagai penghubung antara kelompok nasionalis sekuler dan partai berbasis Islam. Ia aktif memperkuat PSI pada masa kemunduran partai, berperan dalam pembentukan federasi politik kebangsaan (PPPKI), serta membela hak buruh melalui kepemimpinannya di PPPH. Sikap moderat dan konsiliatif Sukiman menimbulkan gesekan internal di PSI, yang berpuncak pada pemecatan dan skorsing dirinya, meskipun banyak pihak menilai langkah tersebut tidak adil. Penelitian ini menegaskan bahwa peran Sukiman layak diangkat sebagai figur nasionalis Muslim yang konsisten memperjuangkan persatuan dan kemerdekaan Indonesia.